Building Better Breakfasts - Linda B. Bobroff; Linda L. Christian; Joy Cantrell Jordan; Carol Freeze (EDIS, 2002)
This unit was developed to inform Extension 4-H agents and home economists, 4-H leaders, and 4-H youth ages 5 to 11 of the importance of eating breakfast, and to give them practical strategies for selecting and/or preparing palatable, culturally acceptable, and nutritious foods for breakfast.